Anthropologists in Films: "The Horror! The Horror!". Issue 2 (14th April 2015) - Weston, Gavin; Lawson, Jamie F.; Blell, Mwenza; Hayton, John
ABSTRACT Drawing upon 53 films featuring fictional representations of anthropologists, we explore in this article the popular depiction and perception of anthropology by examining portrayals of the discipline in film. Finding that 26 of the 53 can be categorized as horror films, we examine the role of anthropologists in these films as experts and mediators for seemingly alien "others" and how this lends itself to frequently heroic depictions. We draw parallels between this work and Conradian voyages into the "heart of darkness" as well as ethical dilemmas and controversies involving real anthropologists. We argue that this body of work represents an excellent opportunity for anthropological teaching while we also implore anthropologists to play more active roles in shaping public perception of the discipline in regard to both analysis and production.